From resilience to sustainability: exploring key stakeholders in agribusiness - Guilherme Fowler A. Monteiro; Silvia Morales de Queiroz Caleman; Júlia Silva Mendes (RAUSP Management Journal)
Purpose – This study aims to investigate agribusiness organizations’ resilience in Mato Grosso do Sul, Brazil, and its implications for sustainability. Design/methodology/approach – Using the Benchmark Resilience Tool model, a multi-case study examined three organizations representing different agribusiness supply chain stakeholders: a rural firm, a farmer’s union and an agriculture cooperative. Each organization successfully navigated recent crises. Findings – Organizations exhibit varying resilience levels. The rural firm prioritizes financial management but lacks governance, necessitating enhancements in governance, risk diversification and resilience training for sustainability. The farmer’s union, with robust governance, can bolster resilience and sustainability via innovation and external partnerships. The cooperative, although proactive, should target resource resilience and knowledge sharing to enhance sustainability. Research limitations/implications – This study focused exclusively on Mato Grosso do Sul agribusiness organizations. Further research could explore other regions and industries to provide a more comprehensive understanding of the relationship between resilience and sustainability. The small sample size is also a limitation. Practical implications – The research identified six strategies through which organizations can enhance sustainability through resilience mechanisms. By integrating the proposed strategies, organizations can navigate the modern business environment while aligning with long-term sustainability goals. Social implications – The lessons learned from this study underscore the pivotal role of resilience in advancing sustainability goals, promoting responsible practices and contributing positively to social facets of organizations. Originality/value – This study contributes to the synergy between organizational resilience and sustainability. It underscores resilience’s pivotal role in achieving sustainability objectives, promoting responsible practices and positively impacting organizations’ environmental, social and economic aspects.